The corona chronicles: Framing analysis of online news headlines of the COVID-19 pandemic in Italy, USA and South Africa - Sumayya Ebrahim (AOSIS, 2022)
Background: The global coronavirus disease 2019 (COVID-19) pandemic, now in its second year, has resulted in a large corpus of literature in a number of disciplines, particularly virology and epidemiology. In contrast, scholarly inquiry in other areas of the health sciences, particularly in media representations and public health communication, is still emerging. Aim: As an integral stakeholder in communication during a pandemic, this descriptive study sought to delineate the media frames of the COVID-19 pandemic in online news headlines in the first month that the COVID-19 was declared a pandemic. Setting: Online news headlines in three global hotspots, namely Italy, the USA and South Africa, during the month of March 2020, were analysed. Methods: Thematic content analysis and epidemic framing typology. Results: The findings indicate that COVID-19 has been internationally portrayed as a lethal pandemic that destroys and disrupts human life. Discursive frames of consequences monopolised its coverage, whilst discursive frames of reassurance were rare, despite the high survival rate. One of the unique findings of this study is that the COVID-19 pandemic coverage included the naming of positive patients, who were thereby made known to the public. Conclusion: Internationally, COVID-19 pandemic coverage used consequence frames that dramatised loss of life instead of deploying frames of reassurance that foreground the high survival rate of this disease. Contribution: Results of the study may help inform public health communication of the COVID-19 pandemic, by offering a detailed description of the frames that journalists use in news headlines, all of which possibly influence public perception of the pandemic. Theoretically, the article has also contributed to the application of epidemic framing typology and has contributed to knowledge in the field of public health communication and the COVID-19 pandemic.